In vitro evaluatinon of oral hygiene commercial products for antimicrobial susceptibility and in combination with the extracts from four spices - Muna, Jalal Ali (2017)
The evolution of microbes, including the development of resistant strains and adaptation, depend on diverse members of the microbial population that can thrive in new condition. Therefore, microbes present remarkable abilities to evolve faster than their hosts do. Dental caries considered as one of the most commonly infectious diseases affecting mankind today, the dissolution of tooth structure by acid produced as a result of the fermentation of dietary carbohydrates by oral bacteria. The antimicrobial susceptibility of medicinal plants including black pepper, black cumin, cinnamon, cardamom on toothpaste and mouthwash against oral isolates for healthcare improvement was studied. Different oral isolates from 50 selected individuals aged 3 to 60 years were obtained from both gender, and a total of 59 bacterial and yeast isolates were collected, purified, and tested against four different commercial medicinal plants extracts for antimicrobial susceptibility profile. A total of 20 different commercial toothpastes and 10 mouthwashes were purchased, and the combined action of the medicinal plants with toothpaste/ mouthwash were studied against oral isolates. We found a higher bacterial population was in the age group of 3–40 years than other two groups, with approximately 44%. Antibiotic susceptibility test against the isolates showed that chloramphenicol had the highest susceptibility effect with 83.2%. In addition, Hemolysin had the highest ability to produce virulence factors (72.88%). The combined action of acetone plant extracts (alone) against oral isolates showed a synergistic effect profile up to 61.02% when combination A (Ci/N) was added. Also, we found the combined action of plant extracts with toothpaste improved the antimicrobial susceptibility up to 90% in case of combination B. While, the combined action of medicinal plants with mouthwash was improved 100% with combination C. The antimicrobial susceptibility of combination toothpaste + mouthwash with plant extracts combination B (TMB) (3 in 1) was higher than combination group at concentration of 10-2 with 95% confidence interval, the effectiveness of toothpaste and mouthwash are not related to the price and age group. The major constituent compounds of plant extracts were identified using GC-MS and demonstrated by TLC analysis which was stearic and palmitic acids exhibited high antimicrobial susceptibility against oral isolates under study. We conclude that the acetonic extract of the combination B (P/N/Ca) with toothpaste showed high susceptibility against oral isolates. Moreover, the combination C (P/N/Ca/Ci) with mouthwash showed high susceptibility, therefore, TMB was the best antimicrobial agent candidate against oral isolates.